INCREASE OF SOCIAL EFFECTIVENESS OF FUNCTIONING OF CREDIT UNIONS OF UKRAINE - Швець , Наталія; Осадець , Олександра (Socio-economic relations in the digital society, 2019)
The article is devoted to the activity of credit unions of Ukraine, namely, the social effectiveness of their functioning. Th e objective content of effi ciency as an estimation category is investigated. The indicators of social effectiveness of credit unions activity are off ered. An analysis was carried out in the context of the proposed indicators of the assessment of the social eff ectiveness of domestic credit unions, which allowed to comprehensively characterize its level and determine the main vectors of further activities aimed at increasing the social eff ect of the work of credit unions in the markets of fi nancial services in Ukraine.
Keywords: credit union; financial services market; efficiency; social efficiency; indicators of social performance evaluation of credit unions